Pengaruh E-Security dan E-Service Quality Terhadap E-Repurchase Intention Dengan E-Satisfaction Sebagai Variabel Intervening Pada Konsumen E-Commerce Lazada di Fisip Undip - Muhammad Mim Farisal Abid; Dinalestari Purbawati (Universitas Diponegoro, 2020)
Business and trade industry has grown rapidly one trading system via internet e-commerce. This research was conducted in order to test the influence of e-security and e-service quality of the e-repurchase intention by e-satisfaction as an intervening variable.This research is quantitative research that uses the type of eksplanatif. Sampling techniques using non-probability sampling and purposive sampling approach. Where the populations are all consumers Lazada in Fisip Undip, while the sample is 100 customers Lazada with certain criteria. The data collection technique using the google form and interview.This study uses quantitative and qualitative analysis of the validity, reliability, correlation coefficient, coefficient of determination, regersi simple and multiple, significance t test and F test with the help of IBM SPSS program (Statistical Product and Service Solutions) version 24. These results indicate that e-security effect on e-satisfaction, e-service qualiti effect on e-satisfaction, e-security and e-service quality influence simultaneously on e-satisfaction.Based on the results Lazada can improve the buying interest of consumers to increase e-service quality with more competent in responding to consumer complaints, and service is fast and good refund. In addition Lazada also need to strengthen the security system so that consumers rely more trustworthy, thereby increasing customer satisfaction, which in turn increases the buying interest of consumers